The Disclosure of Financial and Non-Financial Performance via Narrative Communication: Islamic Bank Annual Report - Fatchul Wachid; Danis Nurul Yunita (Universitas Sebelas Maret, 2019)
The main aim of this study is to compare and analyses the financial performance and non-financial analyses related to the corporate governance of Islamic banks, as reported in narrative communication. It also examines the presence of board impression management in leading the company through level optimism, positive emotion, and so on. The data is obtained from the annual report of two Islamic banks, which are BankIslami Pakistan Limited (BIP) from Pakistan and Warba Bank (WB) from Kuwait during 2012-2016. However, the analyses excluding 2014 because WB only provides a report in the Arabic language. Financial and other non-financial aspects comprising of country analysis, company-level analysis and narrative quality analysis are conducted to investigate the effect of how social system covers nation and company culture, governance structure, and management quality influence the performance of Islamic banks. The comprehensive content analysis method is used to measure the suitability of Islamic value and the impact of the non-financial institution; therefore, it can be the main contribution of this paper. The study found, in the financial aspects, WB has better performance that contributes to IFDI indicators and able to provide information about the source and disbursement zakat fund. Further, in non-financial performance found both Islamic banks still lack information in delivering detail contracts via uqud, environmental aspect, and code ethic of the employee. However, BIP poses bad political affairs in corruption level and role-duality within board structure that can contribute to the lack of transparency and the absence of independence.